206k views
5 votes
What is 8y + 10 − 4 − 5y equal to?

User Esmie
by
6.8k points

2 Answers

2 votes

Answer:

-2

Explanation:

8y+10-4+5y

10+ -4 + 8y + -5y =0

10+ -4=0

6+8y + -5=0

8y + -5y= 3y

6+3y=0

6+ 3y =0

then add -6 at the end of the equation

6+-6+3y=0+-6

continue term

6+-3+3y=0+-6

3y = 0 + -6

combine term

0+3y=0+ -6

3y = 0 +-6

divide each side by 3

and you get -2

User Sinju Angajan
by
5.3k points
6 votes

Answer:

3y+6

Explanation:

Simplify step-by-step.

8y+10−4−5y

=8y+10+−4+−5y

Combine like terms:

=8y+10+−4+−5y

=(8y+−5y)+(10+−4)

=3y+6

User Tirso
by
6.0k points